Evolution of wind musical instruments in the context of the historical development of world musical art - Tao, Han (Professional Art Education, 2024)
The article is to analyze the evolution of the development of wind musical instruments in the context of the history of world musical art. Methods & methodology. The article used the methods of chronological research of the evolution of the development of wind musical instruments in the context of the history of world musical art based on the principles of historicism, objectivity, and a social approach. The scientific novelty of the article lies in the definition of types of wind musical instruments, specification of the classification of natural wind pipes, etc. Results. The study proved that the issue of the evolution of wind musical instruments needs to be updated. Based on the analysis of theoretical-historical and art history literature, it was determined that wind musical instruments (in particular, the trumpet) have undergone a complex evolution from natural varieties to a modern type of chromatic instrument, which provides performers with performances both solo and as part of an orchestra. The trumpet, as one of the varieties of wind musical instruments, has undergone a complex evolution from natural varieties (wooden, metal models) to a modern type of chromatic instrument, which provides performers with performances as soloists, members of various ensembles, and also of various types and orchestras (symphonic, chamber, folk, brass, pop). The role of wind instruments in the development and formation of instrumental music from the Paleolithic era to our time is specified. With the help of comparative and comparative analysis and organological methods, varieties of trumpets as wind musical instruments were revealed. Their classification is considered. Conclusions. So, summarizing the results of the article on the basis of the conducted theoretical-historical and art history background, we can conclude that wind musical instruments have gone through a complex path of evolution from natural varieties (wooden, metal models) to the modern type of chromatic instrument. The problem of the evolution of musical wind instruments in the context of the history of world musical art requires further scientific research. The issue of further research regarding performance on musical wind instruments in the Baroque era is of interest.